2008
DOI: 10.1016/j.rmed.2007.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline as compared to bupropion in smoking-cessation therapy—Cost–utility results for Sweden 2003

Abstract: Estimated costs per QALY gained rated smoking-cessation intervention using varenicline among the most cost-effective life-saving medical treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(94 citation statements)
references
References 30 publications
(48 reference statements)
3
88
3
Order By: Relevance
“…The probability of relapse in the first 10 years post 1 year of cessation is higher than estimates used in some previous models, 62,63,65,66,69 but is in line with other research which suggests that around half of those abstinent at 1 year will relapse to smoking in the next 7 years. 92,93 The annual probability of relapse after 10 years of abstinence was assumed to be 1% in the STA submission and several other applications of the BENESCO model, 62,66,69 all of which based their estimate on a longitudinal study. 91 The authors of this longitudinal study report that 'the (annual) rate of smoking relapse .…”
Section: Relapse Ratessupporting
confidence: 87%
See 1 more Smart Citation
“…The probability of relapse in the first 10 years post 1 year of cessation is higher than estimates used in some previous models, 62,63,65,66,69 but is in line with other research which suggests that around half of those abstinent at 1 year will relapse to smoking in the next 7 years. 92,93 The annual probability of relapse after 10 years of abstinence was assumed to be 1% in the STA submission and several other applications of the BENESCO model, 62,66,69 all of which based their estimate on a longitudinal study. 91 The authors of this longitudinal study report that 'the (annual) rate of smoking relapse .…”
Section: Relapse Ratessupporting
confidence: 87%
“…The BENESCO model has been used in numerous previous evaluations. [63][64][65][66][67][68][69][70][71][72][73] The model uses an annual cycle length and assumes that all smokers die at age 100 years, if death has not been simulated at an earlier age. A hypothetical cohort of 10,000 smokers enters the model, with each smoker assumed to make a single quit attempt, assisted by either varenicline or cytisine.…”
Section: The Conceptual Modelmentioning
confidence: 99%
“…A significant part of the intervention was smoking cessation programmes, either pharmacotherapy 4, 5, 36, 37, 38, 40, 41, 48, 50, 51, 53, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, behavioural therapy 6, 42, 47, 66, 67, 68, 69 or a combination of these 33, 34, 35, 43, 45, 46, 49, 52, 54, 70, 71, 72, 73, 74, 75. Several studies evaluated wider tobacco control interventions 39, 44, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, whereas five studies included both smoking cessation programmes and tobacco control interventions 89, 90, 91, 92, 93.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 23 of 64 studies reported QALY as their main outcome 5, 35, 38, 40, 41, 47, 48, 49, 56, 58, 59, 61, 62, 63, 65, 69, 70, 76, 78, 81, 86, 88, 94, followed by life years (LY) gained ( n  = nine of 64) 33, 43, 46, 66, 67, 68, 73, 74, 89 or a combination of these ( n  = 12 of 64) 4, 6, 35, 36, 37, 39, 42, 44, 57, 77, 80, 83. Five of 64 studies reported disability adjusted life years (DALY) as their main outcome 60, 82, 90, 91, 92, and only four of 64 (incremental) net benefit 52, 53, 55, 71.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation